Evaluation of High-Tech Projects Failure Factors in Afghanistan - Gharanai, Mohammad Hanif; Shahidzay, Amir Kror; Sahnosh, Faqeed Ahmad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Afghanistan ranks among the unfortunate low-income countries lacking viable and consistent electronic government systems, policies, and infrastructure for project execution. Despite the country's adoption of technology, digital systems and ICT projects remain inefficient and prone to vulnerabilities, hindering the delivery of reliable services to both the Afghan government and its citizens. This research assesses various technology-based projects to uncover the underlying causes of failures. The study’s main goals include pinpointing these root causes, exploring the link between policies and ICT initiatives, evaluating platforms and services, and offering recommendations to enhance the environment for the effective and timely execution of ICT projects. A focus on user-centered design is maintained throughout the research process, which employs a mixed-methods approach. This study provides valuable insights for both private and public sectors to implement projects more effectively. We aim for this research to shed light on the factors leading to failures during the planning, design, and implementation phases of projects, encouraging a reflective approach moving forward.